Al-Samāt Al-Ṣarfiyyah fī Al-Lahjah Al-'Arabiyyah Al-Nījīriyyah: Dirāsah Waṣfiyyah - Saleh Kabir; Su’ad Muhammad Abba (Jurnal Al-Maqoyis, 2026)
The Arab tribes locally known as “Shuwa Arabs” constitute part of Nigerian society. These communities settled in Nigeria as a result of ancient migrations from the Arabian Peninsula. They still speak an Arabic dialect that has preserved many inherited linguistic features, which makes Nigerian Arabic a fertile field for linguistic research, especially in the morphological domain, which is regarded as one of the most important keys to understanding word structure and meaning. This study aims to uncover the prominent morphological features of Nigerian Arabic and to show the extent of their conformity with the rules of Classical Arabic morphology, while highlighting the distinctive characteristics unique to the dialect. The study adopts a descriptive-analytical approach by collecting linguistic data from native speakers of Nigerian Arabic, documenting morphological phenomena in vocabulary and structures, and then analyzing them in the light of Arabic morphological rules.The study concludes that Nigerian Arabic largely follows the Arabic morphological system, yet it retains certain distinctive features in verb and noun patterns and word formation. These features can be traced back to ancient Arabic dialects, which indicates the deep Arabic roots of this dialect. The study further concludes that Nigerian Arabic represents a living extension of historical Arabic dialects and has preserved its basic morphological structure, a fact that underscores its importance in comparative and dialectological linguistic studies.